18f-11=48

Simple and best practice solution for 18f-11=48 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 18f-11=48 equation:


Simplifying
18f + -11 = 48

Reorder the terms:
-11 + 18f = 48

Solving
-11 + 18f = 48

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '11' to each side of the equation.
-11 + 11 + 18f = 48 + 11

Combine like terms: -11 + 11 = 0
0 + 18f = 48 + 11
18f = 48 + 11

Combine like terms: 48 + 11 = 59
18f = 59

Divide each side by '18'.
f = 3.277777778

Simplifying
f = 3.277777778

See similar equations:

| (4x+8)=51 | | 63-x=2x+8n | | (X-8)(x-20)=180 | | Y=-4.9(3)*3+17(3)+3.4 | | 8+-6x=-6x+12 | | 5x^2+5x= | | (x^2)(p^2)+xyp-((6)(y^2))=0 | | (12x-4)=(10x+10) | | 8x^2y+36xy-140y=0 | | 15x-(-6x)=(-84) | | (23.89-3x)=14 | | 8-6x=-4x+12 | | 4x+-68+x=40 | | 100x^2+240x+144=0 | | (75x+2600)-(225x-x^2)=0 | | Y=-4.9(3)+17(3)+3.4 | | 8+-6x=-4x+12 | | 5c+10=2c+26 | | 4x^2-48x+54=0 | | -3m+30=6 | | -2x+15=21 | | -9+6=3x | | 6(x+4)-(x+3)=x+1 | | 5xw+16x=0 | | -9=-x+10 | | -3+30=6 | | 60z^3+56z^2-32z=0 | | 14z^4-42z^3+6z^2= | | 4x*-86+x=40 | | 9+4x+7x=75 | | 6-(1+2k)=-(k-1) | | 53a-14=63a+32 |

Equations solver categories